MENINGKATKAN AKUNTABILITAS DANA DESA MELALUI PENGAWASAN BADAN PERMUSYAWARATAN DESA: STUDI KASUS DS. SUMURAGUNG, KEC SUMBERREJO, KAB.BOJONEGORO - Wijaya, Dian (Universitas Islam Majapahit, Indonesia, 2024)
This study aims to describe how to optimize the role of the village consultative body in supervising village funds in Sumuragung Village, Sumberrejo District, Bojonegoro Regency. The Village Consultative Body is an institution that carries out government functions whose members are representatives of the village population based on regional representation and are determined democratically. The implementation of village fund supervision by the BPD has the aim of making the village clean without any fraudulent practices of corruption, collusion, and nepotism. The theory used in this study is to use the eight principles of Good Governance by UNDP (United National Development Programs). In this study, the method used is a qualitative descriptive method. Data collection techniques in this study used observation, interviews, and documentation. Based on the results of the study, the author can conclude that the BPD in Sumuragung Village has carried out its role quite optimally in accordance with the mandate of the Law and Regional Regulations of Bojonegoro Regency, although of the eight indicators of the principles of Good Governance by UNDP, the Sumuragung BPD can only carry out seven indicators for that it is necessary to conduct another evaluation by the Sumuragung Village BPD